Black Box Testing Menggunakan Boundary Value Analysis dan Equivalence Partitioning pada Aplikasi Pengadaan Bahan Baku Batik dengan Pendekatan Use Case - I Dewa Made Widia; Sovia Rosalin; Salnan Ratih Asriningtias; Elta Sonalitha (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
The batik raw material purchase order application is a website application that will be used by Batik MSMEs to be able to help managers make decisions in determining the quantity of raw material orders. To ensure the application meets the expected functional requirements, testing is required. Testing is done using Black Box Testing, which is validating the output from the given data input. Test cases in black box testing can be designed using use cases, because the functional requirements of the application are described in the use case diagram. Test case design that can assist in finding application errors are an important consideration in application testing. There are several types of methods that can be used in determining test cases including Boundary Value Analysis and Equivalence Partitioning. Boundary value analysis can only be used to test data types with range values. Whereas the Equivalence partition is used to exploit all possible data based on defined criteria. So in this study the test was carried out by combining Boundary Value Analysis and Equivalence Partitioning. The test results show the method can find errors from effective applications, this is evidenced by the DRE value obtained of 0.45, which means that 45% of the test cases built did not pass the test.Keyword— Black Box Testing, Boundary Analysis Value, Equivalence Partitioning, MSMEs, Use Case